EVALUATION OF EFFECTIVENESS OF INFANT´S MORTALITY REDUCTION PRACTICES IN AREA COVERED AND NOT COVERED BY THE FAMILY HEALTH' STRATEGY IN GARANHUNS-PE (Fiep Bulletin - online, 2013)
The research aimed to analyse the effectiveness of health care practices turned to reduce infant mortality in the area covered and not covered by the Family Health Strategy (FHS), in the city of Garanhuns-PE. It is an evaluative study with quantitative and qualitative approach, which was based on secondary sources from the Health´s Departament, the Information System of Primary Care (SIAB), through the survey of the number of live births and infant deaths during the years 2007 to 2011 and primary sources, through semi-structured interviews with 15 professionals who are directly connected with the child's health and reducing child mortality. For the treatment of secondary data was calculated the infant mortality rate by the direct method, recommended by Health´s Departament. For analysis and interpretation of primary data were used the technique of the Collective Subject Discourse (CSD), with application of the software Qualiquantisoft.  It was concluded that the majority of intervieweds are unaware of the concepts of mortality and infant mortality rate (IMR), as well as the agenda of health care of the child and reducing child mortality. The children and pregnant women´s care showed up as weakened in areas of study, especially the actions aimed to combat malnutrition, deficiency anemia, postpartum, breastfeeding and integrality´s care in the health system. In both teams, practices are more focused on the biomedical model in disagreement with the recommendations of the agenda and Health´s Departament, which have focused health promotion. It is necessary to reorganize the practices of primary health care with emphasis on reducing child mortality and follow the recommendations of the child mortality reduction´s agenda, as recommended by Health´s Departament.
Keywords: infant mortality; health evaluation; primary health care